2016
DOI: 10.1163/15736121-12341321
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Religiousness and Spirituality on the Relation between Dyadic Sexual and Non-Sexual Communication with Sexual and Marital Satisfaction among Married Jewish Women

Abstract: Moderating effects of religiousness and spirituality on the relations between sexual and non-sexual dyadic communication with sexual and marital satisfaction were examined. Three hundred forty-two married Jewish women responded to self-report measures. Religiousness moderated the relations between both sexual and non-sexual communication with marital satisfaction—for the less religious these relations were stronger in comparison with the more religious—but not with sexual satisfaction. Sexual communication had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Object relations based on early attachment experiences can significantly influence sexual satisfaction in relationships. Research has demonstrated that sexual satisfaction is closely associated with various factors including individual sexual desire, discrepancies in desire between partners, sexual function, and relationship satisfaction (Mark, 2012;Dundon & Rellini, 2010;Lazar, 2016). Studies have shown that sexual satisfaction and relationship satisfaction tend to change together and have a mutually influential relationship (Dundon & Rellini, 2010;Zare et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Object relations based on early attachment experiences can significantly influence sexual satisfaction in relationships. Research has demonstrated that sexual satisfaction is closely associated with various factors including individual sexual desire, discrepancies in desire between partners, sexual function, and relationship satisfaction (Mark, 2012;Dundon & Rellini, 2010;Lazar, 2016). Studies have shown that sexual satisfaction and relationship satisfaction tend to change together and have a mutually influential relationship (Dundon & Rellini, 2010;Zare et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the research conducted by the author, there is at least some research related to the issue of raising the discourse of religious moderation and its relation to contradictory actions with Islamic teachings such as radicalism or terrorism. (Buehler, 2013;Burhani, 2012;Lazar, 2016;Sheikhzadegan, 2020;Tang et al, 2011;You & Yoo, 2016;Zekrgoo & Tajer, 1980). Among the studies above, most of the studies discuss and study the activities of extremist Salafi jihadi groups in several regions of the country.…”
Section: Introductionmentioning
confidence: 99%